Some contextual aspects of the principle of respect for human rights and freedoms in the criminal and executive law, execution and serving of a sentences - Гальцова, О. В. (Problems of legality, 2014)
This article examines the content of the principle of respect for human rights and freedoms in the penal legislation, execution and imprisonment. States that in Ukraine there is reform of the penitentiary system and penal legislation, the effectiveness of which is associated with the implementation of international standards in their treatment of prisoners. Analyzes international instruments in the field of the treatment of prisoners.